Integrated Bioinformatics Analyses of PIN1, CKX, and Yield-Related Genes Reveals the Molecular Mechanisms for the Difference of Seed Number Per Pod Between Soybean and Cowpea - Liu, Lü-Meng; Zhang, Han-Qing; Cheng, Kun; Zhang, Yuan-Ming (Frontiers in Plant Science, 2021)
There is limited advancement on seed number per pod (SNPP) in soybean breeding, resulting in low yield in China. To address this issue, we identified PIN1 and CKX gene families that regulate SNPP in Arabidopsis, analyzed the differences of auxin and cytokinin pathways, and constructed interaction networks on PIN1-, CKX-, and yield-relarted genes in soybean and cowpea. First, the relative expression level (REL) of PIN1 and the plasma membrane localization and phosphorylation levels of PIN1 protein were less in soybean than in cowpea, which make auxin transport efficiency lower in soybean, and its two interacted proteins might be involved in serine hydrolysis, so soybean has lower SNPP than cowpea. Then, CKX gene family, along with its positive regulatory factor ROCK1, had higher REL and less miRNA regulation in soybean flowers than in cowpea ones. These lead to higher cytokinin degradation level, which further reduces the REL of PIN1 and decreases soybean SNPP. We found that VuACX4 had much higher REL than GmACX4, although the two genes essential in embryo development interact with the CKX gene family. Next, a tandem duplication experienced by legumes led to the differentiation of CKX3 into CKX3a and CKX3b, in which CKX3a is a key gene affecting ovule number. Finally, in the yield-related gene networks, three cowpea CBP genes had higher RELs than two soybean CBP genes, low RELs of three soybean-specific IPT genes might lead to a decrease in cytokinin synthesis, and some negative and positive SNPP regulation were found, respectively, in soybean and cowpea. These networks may explain the SNPP difference in the two crops. We deduced that ckx3a or ckx3a ckx6 ckx7 mutants, interfering CYP88A, and over-expressed DELLA increase SNPP in soybean. This study reveals the molecular mechanism for the SNPP difference in the two crops, and provides an important idea for increasing soybean yield.